2011
DOI: 10.2217/fvl.11.79
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Marburg Hemorrhagic Fever

Abstract: Marburg virus belongs to the genus Marburgvirus in the family Filoviridae and causes a severe hemorrhagic fever, known as Marburg hemorrhagic fever (MHF), in both humans and nonhuman primates. Similar to the more widely known Ebola hemorrhagic fever, MHF is characterized by systemic viral replication, immunosuppression and abnormal inflammatory responses. These pathological features of the disease contribute to a number of systemic dysfunctions including hemorrhages, edema, coagulation abnormalities and, ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
159
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(168 citation statements)
references
References 93 publications
9
159
0
Order By: Relevance
“…During midstage disease, patients develop hemorrhagic manifestations, such as gastrointestinal mucosal petechiae and hemorrhage with bloody diarrhea, ecchymoses, and hematemesis. Progression to late stage disease is characterized by convulsions, dementia, severe coagulopathy, systemic shock, and multiorgan failure, often culminating in death (8,(23)(24)(25). The late-stage disease presentation in this model, as evidenced by high viral titers seen in the liver, spleen, and lymphoid tissues and by hematologic changes and coagulopathy, is comparable to the limited data that are available from patients infected with Marburg virus (3,9,24,26,27).…”
Section: Discussionmentioning
confidence: 57%
“…During midstage disease, patients develop hemorrhagic manifestations, such as gastrointestinal mucosal petechiae and hemorrhage with bloody diarrhea, ecchymoses, and hematemesis. Progression to late stage disease is characterized by convulsions, dementia, severe coagulopathy, systemic shock, and multiorgan failure, often culminating in death (8,(23)(24)(25). The late-stage disease presentation in this model, as evidenced by high viral titers seen in the liver, spleen, and lymphoid tissues and by hematologic changes and coagulopathy, is comparable to the limited data that are available from patients infected with Marburg virus (3,9,24,26,27).…”
Section: Discussionmentioning
confidence: 57%
“…Another word, "What is the correct diagnosis for "DIC" that is associated with abnormal coagulation profile?" In Ebola, acute fulminating hepatitis/acute hepatic necrosis, especially multifocal necrosis type, occurs without a good explanation [5,[36][37][38][39][40]. With the "two-activation theory" this can be easily explained by endotheliopathyassociated DIT/VMTD causing hepatic microthrombosis and acute hepatic necrosis syndrome, leading to hepatic coagulopathy [5].…”
Section: Microthrombogenesis and Activated Tf Coagulation Pathwaymentioning
confidence: 99%
“…In addition, phylogenetic analysis of GP gene sequences of EBOV confirmed that epidemic EBOV-Z strains shown close genetic relationships. [7] Ebola Outbreaks According to Ebola Situation Report In West African Countries more than 11,000 deaths and 28500 Suspected Cases are found, Recently there is no conform victim found From Dec 2015 to 6 Jan 2016, due to migration It is spread in European countries, suspected cases found in Spain, Italy and United kingdom, the worldwide Suspected cases shown in Figure 2 (WHO 2016).…”
Section: Ebola Virus Is Precarious Corresponding To Ebola Virus Diseamentioning
confidence: 99%